Lack of Legal Certainty Regarding the Role Of Mineral and Coal Mining Taxes In Environmental Recovery - Triyono Martanto (Faculty of Law, Universitas Pekalongan, 2024)
Post-mining environmental recovery efforts are a must in order to realize mineral and coal mining with a sustainable development perspective as well as ecological justice, in order to realize this, the existence of a mechanism for the availability of a post-mining environmental recovery budget is needed. One of these mechanisms is through mineral and coal mining taxes as referred to in Law Number 28 of 2009 concerning Regional Taxes and Regional Retributions, however, taxes as a mechanism for providing a post-mining environmental recovery budget have not been implemented until now. Especially Lack of Legal Certainty Regarding the Role Of Mineral and Coal Mining Taxes In Environmental Recovery. This paper uses a descriptive explanatory research method. Based on the study conducted, it can be seen that the implementation of mining taxes has not been able to realize ecological justice, this is because tax regulations have not optimally implemented coercive efforts and through criminal law channels so that the culture of tax irregularities and mining tax evasion is high, including mining taxes.